2023
DOI: 10.1128/mbio.00102-23
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Consequences of Polyphosphate Synthesis and Imminent Phosphate Limitation

Abstract: Cells must strike a delicate balance between the high demand of inorganic phosphate (P i ) for synthesizing nucleic acids and phospholipids and its detrimental bioenergetic effects by reducing the free energy of nucleotide hydrolysis. The latter may stall metabolism.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 118 publications
1
3
0
Order By: Relevance
“…cerevisiae. Moreover, it can activate the protein kinase A pathway, which regulates cell growth and several associated physiological properties. In addition, Kim et al reported that phosphate starvation led to reduced accumulation of phosphate-containing nucleotides, nucleoside diphosphates, and nucleoside triphosphates . The results of this study confirm this point.…”
Section: Resultssupporting
confidence: 78%
“…cerevisiae. Moreover, it can activate the protein kinase A pathway, which regulates cell growth and several associated physiological properties. In addition, Kim et al reported that phosphate starvation led to reduced accumulation of phosphate-containing nucleotides, nucleoside diphosphates, and nucleoside triphosphates . The results of this study confirm this point.…”
Section: Resultssupporting
confidence: 78%
“…By contrast, earlier studies based on unbiased mutagenesis, which subsequently received much less attention, had identified mutations in other regions of PHO81 with significant impact on PHO pathway activation ( Ogawa et al, 1995 ; Spain et al, 1995 ; Toh-E and Oshima, 1974 ; Creasy et al, 1993 ; Creasy et al, 1996 ). The situation is complicated by further studies, which found global IP 7 levels to decrease rather than increase upon P i starvation ( Wild et al, 2016 ; Li et al, 2020 ; Lonetti et al, 2011 ; Kim et al, 2023 ). The analytics used in most studies could not distinguish 1-IP 7 and 5-IP 7 , however, leaving open the possibility that an increase of 1-IP 7 might be masked by a decrease of a much larger pool of 5-IP 7 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 39 41 ]. A strong effect of phosphate limitation on glycolysis, early TCA metabolites, such as citric acid, isocitric acid, and oxoglutaric acid, and oxygen consumption has also been reported for Saccharomyces cerevisiae [ 42 ]. The distinct trajectories of the OTR curves under phosphate limitation resemble those previously overserved for Escherichia coli and Hansenula polymorpha [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Corynebacterium glutamicum was able to maintain its growth rate, when extracellular phosphate was depleted, by reducing the internal phosphate content [ 46 ]. Many species of fungi can store excessive phosphate as polyphosphate in their vacuoles [ 42 , 55 , 56 ]. Under phosphate-limited conditions, the stored polyphosphate is degraded and thus buffers the cytosolic phosphate levels.…”
Section: Resultsmentioning
confidence: 99%